PERANCANGAN STANDAR OPERASIONAL PROSEDUR SIKLUS OPERASIONAL PADA PERUSAHAAN STAGGER MEDIA - Gozal, Satrio (Jurnal Performa: Jurnal Manajemen dan Start-up Bisnis, 2017)
The videography industry has a chance for sustainable in Surabaya. Client satisfaction level must upgraded in order to make repeat order for Stagger Media videography service. The purpose of this research is to designing standard operating procedure in operating cycle so company performance suitable with client wish. This research is a qualitative research. The population and sample in this research consist of competitor company, SOP expert, and client Stagger Media. Interview and observation are used to collect research data, while triangulation technique is used to test the validity of the data. Technique analysis data of this research is using operating management, standard operating procedure, design system, and flowchart. Research results design standard operating procedure operating cycle of stagger media when doing produce.